Promoting Students' Creative Thinking Through Activities Exploring The Surrounding Nature: A Stem Project-Based Learning Design For Sets - Adinda Salshabilla Yudha; Helen Novi Antika; Erina Ellen Rusmana; Ahmad Wachidul Kohar (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2023)
This study aims to describe the process and results of the development of STEM-Surrounding-Nature-Exploration (SNE) integrated with PjBL-based learning materials to improve students' creative thinking skills on sets concepts This is developmental research using the Plomp model to develop learning materials in the form of Teaching Modules and Project Worksheets for set materials with a STEM-SNE integrated project learning design. The trial was conducted on 31 grade 7 students at a junior high school in Surabaya, East Java. Data collection and analysis techniques were carried out using validation sheets to determine the validity of the learning materials tested on the validator. A pre-test and a post-test were used to measure effectiveness related to students' creative thinking on set material. In addition, student response sheets were also used to determine the practicality of the learning materials. Results found that the learning device obtained a validity criterion of 92.5% for the Project Worksheet while 91.25% for the validity of the Teaching Module and each was classified as very valid. For effectiveness criteria, it was obtained n-gain of 0.7512 in the limited trial and 0.71 in the class trial and each of them obtained high effectiveness criteria. Learning materials obtain very practical criteria implemented with an average student response acquisition of 85% and 84% for project learning designs.